P146 Who matters to me? - using ecomaps in patient assessment & care. (1st October 2013) - Gallagher, Bernadette
Abstract : When doing good quality assessments for patients at St Joseph's Hospice it was recognised that genograms did not tell the whole story – so I looked to Ecomaps Dr Ann Hartmann developed the ecomap as part of her social work practice in 1975. Initially it was used as a tool to show family life but Dr Hartmann then recognised that it was a useful tool to show a diagrammatic picture of a person's life and helped clients view their situation from an outside perspective. The term eco is derived from the Greek ecology - the pattern of relationships between plants, animals & people to each other & their surroundings. The ecomap is a graphical representation of an individual or family and their interaction with other people & their environment. It is underpinned by the Systems Theory as described by Pincus & Minahan (1973) Informal Systems e.g. family, friends & neighbours. Providing emotional support & advice. Formal systems e.g. clubs, societies & other groups that can provide support. Public systems e.g. hospitals, schools & local government. The systems theory is useful in looking at an individual's systems (their support network) to recognise & promote strengths and to sustain relationships that are under strain, it is at the heart of person centred planning. It is therefore used for assessment, planning & intervention. The ecomap is as individual as the person and a positive is that it can show spiritual domains that are very important to the person to help cope with illness this can include transpersonal beings (angels, demons, ancestors). Ecomaps are now included in St. Joseph's Hospice Core Assessments & each patient's ecomap will be displayed in our Multi-Disciplinary meetings to ensure that the patient & their world are kept the centre of our focus.